A Rare Combination of Clubfoot and Down Syndrome A Case Series and Literature Review - Pokharel, Sabin; Gurung, Yam Prakash; Khatri, Arun; Yonjan, Rajendra; Rajbhandari, Tarun; Banskota, Bibek; Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2024)
Down syndrome (DS) is commonly associated with pesplanovalgus among foot disorders due to hypotonia and joint laxity. Soft tissue contractures around the ankle and foot are implicated as the pathoanatomy in the case of Clubfoot, which is different from DS. Few cases of Clubfoot have been reported in association with DS. We report two cases of Clubfoot in association with DS, which were treated with the ponseti method and gave a good result.